Assessment of Palliative Care in Lung Cancer in Turkey - YUMUK, PERRAN FULDEN (KARGER, 2017)
Objective: To investigate the symptoms of lung cancer in Turkey and to evaluate approaches to alleviate these symptoms. Subjects and Methods: This study included 1,245 lung cancer patients from 26 centers in Turkey. Demographic characteristics as well as information regarding the disease and treatments were obtained from medical records and patient interviews. Symptoms were evaluated using the Edmonton Symptom Assessment Scale (ESAS) and were graded on a scale between 0 and 10 points. Data were compared using the. 2, Student t, and Mann-Whitney U tests. Potential predictors of symptoms were analyzed using logistic regression analysis. Results: The most common symptom was tiredness (n = 1,002; 82.1%), followed by dyspnea (n = 845; 69.3%), appetite loss (n = 801; 65.7%), pain (n = 798; 65.4%), drowsiness (n = 742; 60.8%), anxiety (n = 704; 57.7%), depression (n = 623; 51.1%), and nausea (n = 557; 45.5%). Of the 1,245 patients, 590 (48.4%) had difficulty in initiating or maintaining sleep. The symptoms were more severe in stages III and IV. Logistic regression analysis indicated a clear association between demographic characteristics and symptom distress, as well as between symptom distress (except nausea) and well-being. Overall, 804 (65.4%) patients used analgesics, 630 (51.5%) received treatment for dyspnea, 242 (19.8%) used enteral/parenteral nutrition, 132 (10.8%) used appetite stimulants, and 129 (10.6%) used anxiolytics/antidepressants. Of the 799 patients who received analgesics, 173 (21.7%) reported that their symptoms were under control, and also those on other various treatment modalities (dyspnea: 78/627 [12.4%], appetite stimulant: 25/132 [18.9%], and anxiolytics/antidepressants: 25/129 [19.4%]) reported that their symptoms were controlled. Conclusion: In this study, the symptoms progressed and became more severe in the advanced stages of lung cancer, and palliative treatment was insufficient in most of the patients in Turkey. (C) 2016 S. Karger AG, Basel
Keywords: Lung cancer; Palliation; Palliative treatment; Symptoms; Treatment; QUALITY-OF-LIFE; SLEEP DISTURBANCES; SYMPTOM EXPERIENCE; SUPPORTIVE CARE; PAIN; CHEMOTHERAPY; PREVALENCE; IMPACT